2006
DOI: 10.3130/jaabe.5.113
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Cognition of the Visually Handicapped: Case Study of Geometric Model Spaces with a Center Core

Abstract: Our team previously carried out a series of studies [1][2][3][4] on the spatial cognition of the visually handicapped. From these studies we ascertained that the visually handicapped are able to navigate space by walking across it -in effect, by "taking a shortcut" -to reach their destination. However, under conditions where the visually handicapped are unable to navigate space in this way -because their path has been obstructed by an "obstacle" -it is not so clear how they recognize this space, their position… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani, et al, 2006a). Providing tactile maps, handrails, and door signs have also been shown to help to reduce travel time (Hwang, 2011).…”
Section: Home Modification and Needs Of The Vision Impairedmentioning
confidence: 95%
See 1 more Smart Citation
“…The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani, et al, 2006a). Providing tactile maps, handrails, and door signs have also been shown to help to reduce travel time (Hwang, 2011).…”
Section: Home Modification and Needs Of The Vision Impairedmentioning
confidence: 95%
“…Some studies have investigated environmental conditions with the goal of helping the visually handicapped navigate their surroundings (Kametani, Kishigami, & Chibana, 2006a, 2006bMotlagh et al, 2009;Hwang, 2011). The findings suggested that smaller spaces and right-angle corners are less difficult for the vision impaired to recognize (Kametani, et al, 2006a).…”
Section: Home Modification and Needs Of The Vision Impairedmentioning
confidence: 99%
“…The environment was constructed in a large conference room 11.5×6.2 m 2 with a large oval shape table 7.6×2.1 m 2 placed at its centre representing the environment of 6), 7) . Thirty five blind-folded subjects contributed for extraction of the motion patterns.…”
Section: Experimental Workmentioning
confidence: 99%
“…In the previous studies 6), 7) , such analysis has been mostly through walking locus, interview and sketch maps. However, the real-time path prediction was not included for estimation of motion patterns; and therefore, the results have been classified into a number of fixed patterns without considering the inherent variability of biological systems.…”
Section: Introductionmentioning
confidence: 99%